Detection and identification of etiological agents (Liberibacter spp.) associated with citrus greening disease in Uganda - Kalyebi, A.; Aisu, G.; Ramathani, I.; Ogwang, J.; McOwen, N.; Russell, P. (African Journals Online (AJOL), 2015)
Citrus Huanglongbing (HLB), commonly referred to as citrus greening, is one of the major disease challenges of citrus. In Uganda, there was limited information on Liberibacter spp., the causal organisms of HLB disease, and its psyllid vectors despite the presence of HLB symptoms on citrus. The objective of this study was to identify the Liberibacter spp. and psylla vector species responsible for HLB in Uganda. Other native plant species that could be hosts to pathogens and the psyllid vectors, but are not in the citrus genus, were also investigated. A survey was conducted in 15 citrus growing districts, and symptomatic citrus leaf samples collected, as well as citrus psyllid nymphs and adults for isothermal detection of pathogens in the laboratory. Two types of bacterial pathogens responsible for HLB were detected, namely Candidatus Liberibacter africanus (CLaf), known as the African type; and Candidatus Liberibacter asiaticus (CLas), known as the Asian type. CLaf was found in Mukono and Wakiso districts in Central Uganda and in Mbarara in Western Uganda; while CLas was found in Budaka and Tororo districts in Eastern Uganda. Citrus psyllids, which are the major known disease vectors were present in seven out of the fifteen districts. Psyllid vector identification by morphological means indicated Trioza erytreae, the African psyllid to be the insect vector. Psyllids were common on tangerines (66.7%), Sour Orange (13.3%) and Rough Lemon (13.3%); and least on Washington Navel (6.7%). Three non-citrus plants, Stephania abyssinica (Dill. & A. Rich) walp var. tomentella (Oliv.) Deils (Menispermaceae), Diospyros mespiliformis (Ebenaceae) and Ficus spp (Moraceae) were found to be alternative host plants for the psyllid.